2007
DOI: 10.1007/s10935-007-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

Family Contact and Housing Stability in a National Multi-Site Cohort of Homeless Adults with Severe Mental Illness

Abstract: This study examined associations between family contact and housing stability among 4,778 homeless persons with mental illness who received intensive outreach and case management services through the national multi-site ACCESS project. Ordinary-least squares regression analysis found that, at 12-months post-study entry, greater contact with relatives to whom participants feel close, more frequent telephone contact, and greater satisfaction with family relationships were associated with a greater number of nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…These included permanent supportive housing (PSH; Drake, Yovetich, Bebout, Harris, & McHugo, 1997; Hickert & Taylor, 2011; O'Connell, Kasprow, & Rosenheck, 2012, 2017; Pankratz et al. 2017; Wood, Hurlburt, Hough, & Hofstetter, 1998; n = 6; 28.6%), assertive case management ( n = 2; 9.5%; Pickett‐Schenk, Cook, Grey, & Butler, 2007; Wasylenki, Goering, Lemire, Lindsey, & Lancee, 1993) and critical time intervention (CTI; n = 1; 4.8%). All of these studies evaluated the effectiveness of each intervention on social integration, one on physical integration (Hickert & Taylor, 2011), and none on psychological integration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included permanent supportive housing (PSH; Drake, Yovetich, Bebout, Harris, & McHugo, 1997; Hickert & Taylor, 2011; O'Connell, Kasprow, & Rosenheck, 2012, 2017; Pankratz et al. 2017; Wood, Hurlburt, Hough, & Hofstetter, 1998; n = 6; 28.6%), assertive case management ( n = 2; 9.5%; Pickett‐Schenk, Cook, Grey, & Butler, 2007; Wasylenki, Goering, Lemire, Lindsey, & Lancee, 1993) and critical time intervention (CTI; n = 1; 4.8%). All of these studies evaluated the effectiveness of each intervention on social integration, one on physical integration (Hickert & Taylor, 2011), and none on psychological integration.…”
Section: Resultsmentioning
confidence: 99%
“…After 6‐months of participating, service users reported a statistically significant increase in social integration including the number of: social contacts in the last month; supportive persons; reciprocal relationships; and confidants (Wasylenki et al., 1993). In another study, a large scale evaluation of an intensive case management (ICM) and outreach program called Access to Community Care and Effective Supports and Services that was implemented in 18 sites across the United States, the study authors found that at 12‐months post study entry, participants reported a statistically significant increase in contacts with close family members, more frequent telephone contact with family members, and an increase in satisfaction with family relationships (Pickett‐Schenk et al., 2007). In the only study included in this review that evaluated CTI, a three‐phase intervention delivered to homeless individuals initiated during an institutional (hospital or shelter) admission, the authors found that 12‐months post study entry, there were no significant differences between the CTI and control groups on a measure of social support (de Vet et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximity to and familiarity with service users ensure relatives are often best placed to facilitate early assistance and support sustained engagement, greater accommodation stability, improved social role functioning and use of medication. [5][6][7][8][9][10] Such proximity is not without cost as 29-60% of relatives have been demonstrated to suffer from significant psychological distress. 11 The consequences of excessive burden and stress can impact on the psychological well-being of both service users and relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Unpaid caregivers save the Australian, British and American health and social care systems approximately $30.5, 2 £119 3 and $375 4 billion per annum, respectively. Proximity to and familiarity with service users ensure relatives are often best placed to facilitate early assistance and support sustained engagement, greater accommodation stability, improved social role functioning and use of medication 5–10 . Such proximity is not without cost as 29–60% of relatives have been demonstrated to suffer from significant psychological distress 11 …”
Section: Introductionmentioning
confidence: 99%